Mapping Potential Commercialization of Research Results Through Valuation and Technology Readiness Levels - Octavia, Ade; Ekasari, Novita; Surya Hartati, Dwi; Habibi, Akhmad (Dinasti International Journal of Management Science, 2024)
Downstreaming the results of ’lecturers’ research is a strategic activity to improve the performance of a higher education institution (HEI) which requires research on mapping the commercialization potential. This research aims to understand the role of research centres in the commercialization process and increasing start-ups at one Indonesian university, Universitas Jambi (UNJA). Besides, this research maps the potential for commercialization assessed from the valuation system and technology readiness levels (TRL). This research is important for achieving the institution vision of " a world-class entrepreneurship university based on agroindustry and environment”. The results are expected to contribute to empirical thinking for formulating research policies. This type of research is descriptive qualitative, with research lecturers and leadership elements as the informants. The TLR of the research is 5, and the research output is in the form of publications in indexed international journals, international seminar certificates, and registered textbooks. The results of the study indicate that policies and programs to increase the commercialization of research results have been carried out. A start-up planning and valuation system has also been done and has a good opportunity to increase the commercialization of research results.